1999
DOI: 10.1097/00002508-199912000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Premature Infant Pain Profile in the Clinical Setting

Abstract: This study demonstrates that the PIPP is a pain measure with good construct validity and excellent inter- and intrarater reliability for the assessment of procedural pain of preterm and term infants in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
166
0
8

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(180 citation statements)
references
References 20 publications
6
166
0
8
Order By: Relevance
“…Total score equal to or lower than six is considered as no pain or minimal pain and a score greater than 12 is classified as moderate or intense pain. The PIPP was validated for sensibility and specificity and it is adequate to assess pain in newborn infants undergoing procedures and to diagnose pain in full term and preterm newborn infants (3)(4) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total score equal to or lower than six is considered as no pain or minimal pain and a score greater than 12 is classified as moderate or intense pain. The PIPP was validated for sensibility and specificity and it is adequate to assess pain in newborn infants undergoing procedures and to diagnose pain in full term and preterm newborn infants (3)(4) .…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, neonates' painful response to heel lance and venepuncture were assessed by two researchers in the clinical setting and later through video recording by two experts in neonatal facial coding, with excellent inter and intrarater reliability (4) , corroborating for application in the clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…Results indicated the appropriate validation and excellent intra and inter-observers agreement degree for the use of the instrument in a clinical scenario. 11 In order to validate its employment in measuring post-surgery pain, a study was performed with the objective of comparing the convergent validity of PIPP and Crying, Requires oxygen to keep saturation>95%, Increased vital signs, Expression, Sleepless Scale (CRIES), 12 an instrument specifically developed for postsurgery pain assessment. A total of 51 NBs at the gestational age between 28 and 42 weeks were included in this study and results demonstrated both instruments as valid for assessing pain in the first 72 hours after surgery for premature and full term NBs'.…”
Section: Introductionmentioning
confidence: 99%
“…13 Therefore, through its initial validation and later studies, the instrument demonstrated robust psychometric properties: moderate internal consistency (α=0.59-0.76), appropriate intra (α=0.89-0.91) and inter (α=0.95-0.97) observers agreement, in addition to adequate construct validity. [10][11]13 Moreover, PIPP psychometric adequacy was proved in a study evaluating 62 publications, related to the instrument, from which 14 tested the PIPP psychometric properties. 14 This scale is frequently employed in studies for the development of new instruments for neonatal pain assessment, as convergent validity is tested.…”
Section: Introductionmentioning
confidence: 99%
“…Various pain scores now make it possible to assess and grade the effects of analgesia in the neonate. [4][5][6] The Premature Infant Pain Profile (PIPP), the assessment measure developed specifically for preterm neonates with the most validation studies in this population, 7 includes assessment of facial expression as well as physiological measures in the context of GA and neonatal state.…”
Section: Introductionmentioning
confidence: 99%